ON TORTIOUS LIABILITY AND THE CIVIL LIABILITY OF PERSONS NOT ENDOWED WITH REASON IN THE CONTEXT OF THE CURRENT CIVIL CODE - Radu, Motica; Florin, Mangu (Anales Universitatis Apulensis Series Jurisprudentia, 2012)
The drafters of the current Civil Code have also included the provisions concerning the ability to bear tortious liability in the regulation of tort liability for one’s own acts, in the Arts. 1366-1368. The first legal text sets the framework of the tort liability of minors and persons interdicted for their own acts. According to para. 1 of Art. 1366, the minor under the age of 14 or the person interdicted is not liable to reparation for the injury caused by an act, unless it is proved that he was endowed with reason when he committed the respective act. It is thus worth noting that the solution adopted by the editors of the new Civil Code regarding minors under the age of 14 is identical to that enshrined in our legislation nearly six decades ago, under Art. 25 para. 3 of the Decree no. 32/1954, instituting, in this respect, a rebuttable legal presumption of lack of reason that can be overturned by evidence to the contrary. The innovation consists however in the extension of this solution to the mentally disordered persons interdicted, whose ability to bear tortious liability is not envisaged by our country’s current legislation. Key words : the ability to bear tortious liability, tort liability of minors, tort liability of persons interdicted for their own acts, legal presumption of lack of reason